ANALISIS PERMINTAAN KOMODITI CABAI MERAH DI KABUPATEN SIDENRENG RAPPANG - Rasidin, Rasidin; Nuddin, Andi; Irmayani, Irmayani (Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Muhammadiyah Siddenreng Rappang, 2022)
The demand for red chili in Sidrap Regency is quite increasing, although in 2019 and 2020 there is a decrease in the number of requests for this commodity which is thought to be a result of the reduced area of planting land and the Covid-19 pandemic. This study aims to analyze the influence of the factors that influence the demand for red chili and the elasticity of demand for these commodities in this area. The instrument used in the form of a questionnaire which was analyzed by multiple linear regression through SPSS Version 28. The results showed that the factors that influenced the demand for red chili in Watang Pulu District, Sidrap Regency were the price of red chili itself, the price of curly red chili, and family income. . While the number of family members does not have a significant effect. The elasticity of demand for red chili in this area is inelastic where the price of curly red chili becomes a substitute commodity for red chili which is known to be not an inferior good in this area.